Evaluation of the operator learning curve for radiofrequency ablation for atrioventricular nodal reentrant tachycardia - KEPEZ, ALPER (My University, 2023)
Aim The aim of this study was to determine the average minimum number of slow pathway ablation procedures required to reach a steady success rate among inexperienced operators.Material and Methods We analyzed the consecutive AVNRT ablation procedures of three inexperienced operators for the rate of operational success and complications.Results Operators performed a total of 156 AVNRT ablation procedures. There was no statistical significance between the three operators regarding the rate of success (p=0.69) and complications. There were significant differences between the operators in terms of procedure time, fluoroscopy time, and cumulative air kerma. The variability of procedure time and cumulative air kerma, both among three operators and within each operator, decreased significantly after the 25th case. Each operator was analyzed individually for the probability of success as related to the cumulative number of ablations. All trainee operators reached a success rate of 90 % at the 27th procedure.Conclusion An average of 27 slow pathway ablation procedures should be performed by a beginner operator to achieve proficiency.
Цель Целью данного исследования было определить среднее минимальное количество процедур аблации медленного пути, необходимое для достижения устойчивого успеха у неопытных операторов. Материал и методы Мы проанализировали последовательные процедуры аблации атриовентрикулярной узловой реципрокной тахикардии (АВУРТ) тремя неопытными операторами на предмет успешности операции и наличия осложнений. Результаты В общей сложности операторы выполнили 156 процедур аблации АВУРТ. Не было статистически значимых различий между тремя операторами в отношении частоты успеха (p = 0,69) и развития осложнений. Были значительные различия между операторами с точки зрения времени процедуры, времени рентгеноскопии и кумулятивной воздушной кермы. Вариабельность времени процедуры и кумулятивной воздушной кермы как среди трех операторов, так и внутри каждого оператора значительно уменьшилась после 25-го случая. Каждый оператор анализировался индивидуально на предмет вероятности успеха по отношению к совокупному количеству аблаций. Все операторы-стажеры достигли успеха в 90% на 27-й процедуре. Вывод Начинающему оператору необходимо выполнить в среднем 27 процедур аблации медленного пути, чтобы достичь устойчивого показателя успеха процедуры.